Volatile organic compounds emitted by Megaplatypus mutatus associated fungi: chemical identification and temperature-modulated responses by the ambrosial beetle - Ceriani Nakamurakare, Esteban Daniel (2024)
Background: In ambrosia and bark beetles–fungi interaction, volatile organic compounds (VOCs) play a central role in mediating various aspects of community dynamics of beetles and/or fungi. These functions include facilitating beetle habitat location, mate identification, and fungal partner differentiation. However, the understanding on this context remains limited, especially in the globally distributed subfamily Platypodinae, which comprises predominantly ambrosia beetles. There is a lack of chemical data on ambrosia fungi from native South American species. This study addresses this gap by characterizing VOCs from twelve fungal species associated with Megaplatypus mutatus and assessing species-specific behavioral responses during dispersal. Methods: Fungal VOCs were collected by gas chromatography–mass spectrometry combined with solid-phase microextraction and Y-olfactometry assays of males and females were performed at dispersal stage. Statistical analyses involved: non-metric multidimensional scaling multivariate plot and PERMANOVA test, a cluster analysis through unweighted pair group method with Jaccard index, and finally, a chi-square goodness-of-fit test for beetle behavioral assays. Results: We identified 72 VOCs from the fungal species isolated from M. mutatus galleries, exocuticle, and gut. The olfactory behavior of M. mutatus demonstrated its capacity to discriminate between volatile profiles, showing a preference for either the fungus or the control source. Our results also enhance the understanding in a chemotaxonomic context and in the behavioral responses of M. mutatus revealing the beetle's remarkable low temperature tolerance and its capability to maintain mobility and orientation toward volatile sources even after zero-degree Celsius exposure. Conclusion: This study presents a comprehensive insight into fungal VOC profiles, emphasizing the sources of isolation within pest associated fungi, as well as its symbiotic species from the Raffaelea genus. In conclusion, our findings suggest that Megaplatypus mutatus exhibits a general aversion to its fungal VOCs symbiont. However, a notable exception arises when the beetles are pre-exposed for 48 h to freezing conditions, highlighting the beetles' ability to withstand freezing conditions as adults and to exhibit altered responses to their fungal associates under these circumstances.